FRI0119 The Association between QTc Interval and Myocardial Abnormalities in Rheumatoid Arthritis Patients without Cardiac Symptoms, by Assessed Using Cardiac Magnetic Resonance Imaging. (15th July 2016) - Nishiwaki, A.; Kobayashi, H.; Nagasawa, Y.; Sugiyama, K.; Ikumi, N.; Nozaki, T.; Inomata, H.; Karasawa, H.; Shiraiwa, H.; Iwata, M.; Kitamura, N.; Takei, M.
Abstract : Background: Individuals with rheumatoid arthritis (RA) have a twofold higher risk of developing sudden death than age and gender matched controls without RA. The underlying mechanisms have not yet been clarified. Objectives: The aim of this study was to prospectively investigate the association of myocardial involvement assessed by a cardiac magnetic resonance imaging (CMR) and the QTc interval in RA without cardiac symptoms. Methods: RA patients and control subjects with no history and/or clinical findings of systemic and pulmonary hypertension, coronary artery disease, valvular heart disease, atrial fibrillation, diabetes mellitus, and dyslipidemia were enrolled and underwent CMR. RA patients received conventional synthetic disease-modifying antirheumatic drugs (csDMARDs) or biologic DMARDs (bDMARDs). Late gadolinium enhancement (LGE) was obtained for the assessment of myocardial fibrosis. Using a black-blood T2-weighted image (T2-WI), myocardial inflammation could be assessed. The QTc intervals were manually measured on a 12-lead electrocardiogram, according to standard criteria. The QTc interval of 440 ms was considered to be prolonged in this study. We compared the patients and controls in terms of prevalence of CMR abnormalities and the QTc interval, and explored possible associations between CMR abnormalities and the QTc interval. Results: Sixty-seven patients (mean age, 54.2 ± 1.7 years; 89% female) and 30 controls (mean age 53.6 ± 2.5 years; 87% female) were enrolled. Thirty-one RA patients received csDMARDs [25, methotrexate (MTX) (9.7±2.1 mg); 7, other drugs)] and 36 RA patients received bDMARDs [(15, infliximab; 15, tocilizumab; 6, abatacept, plus MTX respectively. (9.6±1.4 mg)]. The control group showed no myocardial abnormalities. Twenty seven RA patients (40%) demonstrated myocardial abnormalities. T2-WI was seen in seven RA patients (10%). LGE-positive was found in 20 RA patients (30%), six of whom also demonstrated T2-WI. All RA patients and control patients displayed a normal QTc interval. However, there was significant difference in the QTc interval between the control and LGE-positive (p=0.013). Also LGE-positive was significant higher in the QTc interval than LGE -negative. LGE-positive was associated with the QTc interval. The use of bDMARDs was significantly associated with LGE-negative findings (p=0.001) and the QTc interval. (p=0.001). High titer of anticitrullinated protein antibodies was associated with the QTc interval (p=0.04). Receiver operating characteristic analysis showed the QTc interval reliably detected myocardial abnormalities (area under the curve 0.898; 95% confidence interval, 0.830–0.900). Considering patients with RA and a normal QTc interval and using a cutoff of 420 ms, sensitivity and specificity were 91% and 70% in the detection of myocardial abnormalities. Conclusions: Subclinical myocardial inflammation and fibrosis are common in active RA patients without cardiac manifestation. Abnormal CMR findings were associated with a QTc interval. Even if the QTc interval is normal, we should keep in mind the possibility of subclinical myocardial involvement in RA. Disclosure of Interest: None declared